Engagement and Well Being of Students of Vocational Education - Candeias, Cláudia (2015)
Recently, it has been observed an increased theoretical interest and research in relation to the engagement of the student in activities and school contexts, as a possible explanation for the high dropout rates and poor academic results. It is, therefore, that joining this theme so actual and complex of understanding is a risky decision but simultaneously also innovative and rewarding because of the contributions that may arise. Anchored in the theoretical framework of the engagement of Jimerson & Lam (2008) model, this article reflects part of the study conducted under the engagement of students in vocational education at school. Given this multidimensionality, we sought to understand the possible changes of causal variables: well-being and engagement. This option builds on the theoretical evidence and it shows that is extremely important to study the influence of various factors on the existence of more or less well-being and ability to adapt to each subject. Connecting with other constructs such as engagement, since this is a key means by which the students develop feelings about their peers, as his/her teachers and the institutions that give direction of connection and belonging affiliation, while simultaneously offering them opportunities for learning and development. One can, then, empirically conclude that if his/her adaptation is viewed positively, the consequences to the well-being level will be emphasized. Since working this connection (with the engagement), there is an interaction between the emotional and cognitive processes, that is to say, if on one hand the emotion cognitive processes are activated, on the other hand, the emotion also influences the type of information processing the individual runs, which has behavioral implications. In Portugal, and as a way to integrate the prospects of conceptualization of the construct of well-being, Bizarro built a model that served as the basis for the development of an instrument to assess psychological well-being in adolescence, a multidimensional model that includes subjective components which include emotional and cognitive areas. Looking, then, to understand the relationship between engagement and well-being there were used the scale the Student Engagement in School - EEEE (2012 version) and the Scale of Psychological Well-Being for Adolescents (EBEPA). Linear regression model, with the assumptions of normal distribution and homoscedasticity of residuals were validated through the interpretation of PP and Scatterplot graphs were created. In what concerns to the model (dependent variable: psychological well-being independent variable engagement), it appears that it is a fitted model F (4) = 125.444, p = 000 (statistically significant regression). With the exception of engagement, all variables are considered statistically significant for explaining the psychological well-being. At the level of multicollinearity and the values of tolerance and VIF is concluded that there is a given R2a =, and R2 = 494, 498, the linear regression explains 50% of the variance, that is, a good percentage (half) of the variability of the psychological well-being (F (4) = 125.444, p =, 000). These data allowed us to understand the relationships that are established between the study variables, however, it is necessary to investigate further more the multidimensionality of engagement.